2021
DOI: 10.1097/iae.0000000000003093
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of Vitreomacular Traction in Eyes With Diabetic Retinopathy and Factors Associated With Spontaneous Release

Abstract: The aim of this study was to determine the natural course of vitreomacular traction (VMT) in patients with diabetic retinopathy and to evaluate the factors associated with VMT relief.Methods: Seventy-four eyes of 65 patients with VMT accompanying diabetic retinopathy were evaluated retrospectively. The presence of intravitreal injection and the presence of panretinal photocoagulation were obtained from the medical records of the patients. Spontaneous release of VMT, the horizontal length of vitreomacular tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Almeida et al 5 found this to be significant. Garip et al 14 did not observe a significant difference in IVI between their released and persistent VMT groups, but did find spontaneous release occurred in a shorter period in cases with IVI. Our meta-analysis showed no significant difference in previous IVI between the released and persistent VMT groups.…”
Section: Predictive Factors Of Vmt Release Garg Et Al 1227mentioning
confidence: 79%
See 4 more Smart Citations
“…Almeida et al 5 found this to be significant. Garip et al 14 did not observe a significant difference in IVI between their released and persistent VMT groups, but did find spontaneous release occurred in a shorter period in cases with IVI. Our meta-analysis showed no significant difference in previous IVI between the released and persistent VMT groups.…”
Section: Predictive Factors Of Vmt Release Garg Et Al 1227mentioning
confidence: 79%
“…Eighteen studies underwent full text review, and, ultimately, 12 were included (Figure 1; Table 1). [4][5][6][9][10][11][12][13][14][15][16][17] Overall, 934 eyes were included; 104 eyes came from prospective studies (n = 3 studies) and 830 from retrospective studies (n = 9). Mean age was 70.0 years old, 37.2% of patients were men, and mean follow-up was 22.0 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations